2021
DOI: 10.1186/s13012-020-01077-w
|View full text |Cite|
|
Sign up to set email alerts
|

Incentivizing appropriate malaria case management in the private sector: a study protocol for two linked cluster randomized controlled trials to evaluate provider- and client-focused interventions in western Kenya and Lagos, Nigeria

Abstract: Background A large proportion of artemisinin-combination therapy (ACT) anti-malarial medicines is consumed by individuals that do not have malaria. The over-consumption of ACTs is largely driven by retail sales in high malaria-endemic countries to clients who have not received a confirmatory diagnosis. This study aims to target ACT sales to clients receiving a confirmatory diagnosis using malaria rapid diagnostic tests (mRDTs) at retail outlets in Kenya and Nigeria. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…15,16 While extensions of constrained randomization to three-arm parallel cRCTs were recently pursued, 1,2 investigations on the choice of design parameters are currently limited, and the statistical tests previously considered were restricted to linear mixed models. 2 Motivated by a recent multi-arm cRCT, 7 we provided a detailed discussion of the implementation of constrained randomization with alternative balance metrics (the maximum pairwise 2 metric and the maximum Mahalanobis distance metric) for multi-arm cRCTs. For statistical inference under constrained randomization, we additionally developed novel permutation tests for two types of null hypotheses describing the comparative effectiveness of multiple treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 While extensions of constrained randomization to three-arm parallel cRCTs were recently pursued, 1,2 investigations on the choice of design parameters are currently limited, and the statistical tests previously considered were restricted to linear mixed models. 2 Motivated by a recent multi-arm cRCT, 7 we provided a detailed discussion of the implementation of constrained randomization with alternative balance metrics (the maximum pairwise 2 metric and the maximum Mahalanobis distance metric) for multi-arm cRCTs. For statistical inference under constrained randomization, we additionally developed novel permutation tests for two types of null hypotheses describing the comparative effectiveness of multiple treatments.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in Section 3, different types of hypotheses could be of interest in multi-arm parallel cRCTs. 34 We specified a set of three hypotheses (see Table 2) based on model (7) where there is one control condition and two treatment conditions. We adopted a hierarchical approach and specified a global hypothesis comparing all three arms at once as the first step.…”
Section: Null Hypotheses and Multiplicity Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ] the authors reported a correction to their published study protocol.…”
mentioning
confidence: 99%
“…The purpose of this correction is to update the design of one of the two linked cluster randomized trials (CRTs) in our study protocol entitled “ Incentivizing appropriate malaria case management in the private sector: a study protocol for two linked cluster randomized controlled trials to evaluate provider- and client-focused interventions in western Kenya and Lagos, Nigeria” [ 1 ] and to provide justification for a lower target sample size in the other trial. This study included a CRT enrolling clusters (retail outlets) into four treatment arms in Nigeria using estimated sample sizes based on malaria prevalence and testing rates in the published literature.…”
mentioning
confidence: 99%